Stakeholder adoption of e-government services driving and resisting factors - Shareef, Mahmud Akhter 1966-; Kumar, Vinod; Kumar, Uma; Dwivedi, Yogesh K. (Premier reference source, 2011)
"This book examines the stakeholders of e-government and reveals the stages of growth or service maturity levels, shedding light on the paradigms and fundamental discourses of the e-government adoption process" - Provided by publisher